2000
DOI: 10.7326/0003-4819-133-8-200010170-00009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Type 2 Diabetes Mellitus among Persons with Hepatitis C Virus Infection in the United States

Abstract: In the United States, type 2 diabetes occurs more often in persons with HCV infection who are older than 40 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
275
5
11

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 620 publications
(315 citation statements)
references
References 20 publications
24
275
5
11
Order By: Relevance
“…This finding is consistent with the report of Caronia et al, 7 but not with that of Mason et al 6 or Mehta et al 8 Mason et al 6 and Mehta et al 8 found that HCV infection and age were independent predictors of DM, indicating that cirrhosis was not an independent risk factor for diabetes in their population. In our study, HCV infection was not an independent variable (P ϭ 0.053), although the calculated relative odds ratio for DM was 1.61 times higher in patients with HCV than in those with HBV.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with the report of Caronia et al, 7 but not with that of Mason et al 6 or Mehta et al 8 Mason et al 6 and Mehta et al 8 found that HCV infection and age were independent predictors of DM, indicating that cirrhosis was not an independent risk factor for diabetes in their population. In our study, HCV infection was not an independent variable (P ϭ 0.053), although the calculated relative odds ratio for DM was 1.61 times higher in patients with HCV than in those with HBV.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study from the United States has also indicated that in persons with HCV infection, type II DM occurs more often in those who are older than 40 years of age. 8 However, this kind of study has not been reported among Japanese populations, as far as we know.…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, patients with viral liver cirrhosis were the largest group included in both previous studies assessing cardiovascular disease in cirrhosis-2/3rds of the total number of patients in both studies [4,12] compared with 17% in the current one. Hepatitis C has been reported to be related to type 2 diabetes mellitus [29,30], but data on a possible link with cardiovascular disease is controversial. Although the results of some studies suggest that hepatitis B and C infection may be independent risk factors for carotid atherosclerosis [31,32], these findings have not been confirmed by others who have shown that chronic viral hepatitis may help prevent from atherosclerosis in the carotid arteries [33].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports followed along this line, from the same group and others. The trend to accept a positive association between diabetes and HCV infection seems to have been triggered by a population-based study in the United States, 12 in which a solid association was found between them. The association between diabetes and HCV infection, however, is confounded by factors such as the development of cirrhosis, obesity, and older age, which are common in patients with hepatitis C; these factors could make it difficult to prove this association to be real.…”
Section: Diabetes May Also Be a Manifestation Of Hcv Infectionmentioning
confidence: 96%